Risk Of Istishna Contracts In Sharia Commercial Banks - Indra Hidayatullah; Maulana Ainul Yaqin (Muhasabatuna : Jurnal Akuntansi Syariah, 2022)
The Indonesian banking crisis in 2007 made the economic turmoil in Indonesia unstable. In situations and circumstances like this, financing risk is needed which is an important factor in realizing a sound banking system. However, the regulations, especially regarding the risk of banking financing, are in fact not sufficient to guarantee the banking system is free from all problems, especially in istisna financing.